Inverator Starting Energy Saver Design For Electric Power Efficiency In Water Pumps - Faisal Irsan Pasaribu; Noorly Evalina; Partaonan Harahap (Journal of Electrical Technology UMY, 2021)
The use of a Water Pump at the initial start is the use of electricity with a large capacity which sometimes faces various kinds of efficiency problems. These problems include an increase in current that occurs in the channel by improving the quality of electric power, especially in the electrical system in the area of the use of the Water Pump, which is expected to be able to improve the quality of electric power. The purpose of the research was to design an inverter starting energy saver as an effort to improve power quality for electricity savings, electric power efficiency in water pumps. This improvement is also expected to be able to reduce the cost of using electricity bills, especially in the use of water pumps. To be able to carry out the improvement of the quality of the electric power, it is necessary to calculate the active power and apparent power when the water pump is used. After performing these calculations, the installation of the inverter starting circuit saver electricity will be used. By carrying out these steps by installing a series of inverters that can improve the quality of electrical power. And by using the inverter circuit starting Energy saver, it is clear that it produces an active power efficiency value of 82% of the active power before using the 272 Watt inverter circuit and active power after using the 223.9 Watt inverter circuit, and also produces an apparent power efficiency value of 83% before using the circuit. inverter 275.18 VA and apparent power after using the inverter circuit 227.94 VA